The Design Of The Idea Of Judicial Preview Authority Of The Constitutional Court In The Indonesian Constitutional System - Simamora, Janpatar; Manik, Risma (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Adopting the authority of judicial review in the context of testing laws against the Constitution carried out by the Constitutional Court should be welcomed as positive progress for institutionalizing the authority of judicial review itself. In its implementation so far, the authority of judicial review has received serious attention, as evidenced by the number of laws submitted for review in the Constitutional Court. To streamline the authority to review regulations by the Constitutional Court, it is necessary to adopt a model of judicial preview authority, namely testing draft laws, so that when they are passed, they are no longer legally problematic. This research is normative juridical research using various literature materials as the main study. The results show that the idea of adopting the authority of judicial preview is urgently needed. It is based on the consideration that so many laws are problematic both in terms of content and formation process. On the other hand, the authority of the Constitutional Court is only limited to the authority of judicial review, making it less appropriate in the context of the efficiency of judicial review of laws. Given the urgency of the application of judicial preview authority by the Constitutional Court, it is necessary to consider efforts to amend the 1945 Constitution by adding the phrase â€œtesting draft laws against the Constitutionâ€ in the article governing the authority of the Constitutional Court as practiced in other countries such as France.